Total Serum Level of Calcium and Ion Calcium is Lower in Hypotonic Uterine Inertia - Wattimury, Josef (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objectives: To know the correlation between total and ion serum calcium level with the uterine contractility of laboring patient. Methods: This is a cross-sectional analytic correlative study measuring the strength of correlation of total and ion calcium serum level between groups with hypotonic uterine inertia - and normal labor. Each group consists of 20 subjects who met inclusion criteria and presented to Dr. Hasan Sadikin Hospital in August - September 2012. Statistical analysis was performed by using Eta (Î·) coefficient. Results: Mean total calcium serum level on hypotonic uterine inertia is 6.66 mg/dl, while mean of total calcium serum level on normal labor is 8.56 mg/dl, with Eta (Î·) correlation coefficient 0.721. Mean ion calcium serum level on hypotonic uterine inertia is 4.14 mg/dl, while mean of total calcium serum level on normal labor is 4.92 mg/dl, with Eta (Î·) correlation coefficient 0.802. Conclusion: Total serum level of calcium and ion calcium in hypotonic uterine inertia is lower than the level of which in normal labor. There is a strong correlation between total and ion serum calcium level with uterine contractility, the Eta (Î·) correlation coefficient are 0.721 and 0.802 respectively. [Indones J Obstet Gynecol 2013; 1-3: 145-8] Keywords: hypotonic uterine inertia, ion serum calcium level, normal labor, total serum calcium level